Progress in optics. - Wolf, Emil (Elsevier, 2006)
Optical technology is essential to communications and medical technology. K.K. Sharma has written a comprehensive volume on optics. Beginning with introductory ideas and equations, Sharma takes the reader through the world of optics detailing problems encountered, advanced subjects, and actual applications. Elegantly written, this book rigorously examines optics with over 300 illustrations and several problems in each chapter. The book begins with light propagation in anisotropic media considered much later in most books. Sharma has started with this because it provides a more general and beau.